Tailoring graphene reinforced thermoset and biothermoset composites - Nur Bazilah, Thalib; Siti Noor Hidayah, Mustapha; K. F., Chong; Rohani, Mustapha (Walter de Gruyter, 2020)
The surge of knowledge among researchers pertaining to the excellent properties of graphene has led to the utilisation of graphene as a reinforced filler in polymer composites. Different methods of graphene preparation, either bottom-up or top-down methods, are important requirements of starting materials in producing reinforced properties in the composites. The starting graphene material produced is either further functionalised or directly used as a filler in thermoset polymer matrixes. An effective interaction between graphene and polymer matrixes is important and can be achieved by incorporating graphene into a thermoset polymer matrix through melt mixing, solution mixing or in situ polymerisation processes. In addition, by taking into consideration the importance of green and sustainable composites, the details of previous work on graphene reinforced bio-thermoset polymer matrixes is discussed. The resultant mechanical and thermal properties of the composites were associated to the chemical interaction between the graphene filler and a thermoset matrix. Exploration for further variations of graphene polymer composites are discussed by taking the reinforcement properties in graphene composite as a starting point.